Boundary control of marine risers with bending couplings - Nguyen, T.; Do, Khac Duc; Pan, J. (IEEE, 2012)
The aim of this paper is to design a boundary controller at the top end for global stabilization of two-dimensional marine risers under environmental disturbances. Based on the energy approach, equations of motion of the risers including bending couplings are derived. Due to these couplings, the riser dynamics exhibit mutual effects between transverse motions. The Lyapunov direct method is used to design the boundary controller. Stability analysis of the closed-loop system is carried out using the Lyapunov stability theory. Numerical simulations illustrate the results.